Financial management in business - Velykyi, Dmytro (My University, 2014)
Financial Management is one of the key disciplines necessary for the successful management of business corporations and other organisations
Keywords: financial management; business; фінансовий менеджмент; бізнес; финансовый менеджмент; бизнес